Towards a framework for lean operations in product-oriented product service systems. (May 2015) - Resta, Barbara; Powell, Daryl; Gaiardelli, Paolo; Dotti, Stefano
Abstract: More and more companies are beginning to move beyond manufacturing as a sole source of profit by offering integrated bundles of physical goods and services. This phenomenon has become popularly known as servitization, or the establishment of product–service systems (PSSs). Additionally, since the success of the Japanese after WWII and the subsequent popularization of the term "Lean Production" in the 1990s, lean too has almost become a nirvana for the majority of producers. Lean has also found its way into service operations, yet there is an apparent lack of knowledge when it comes to combining the successes associated with lean thinking with the potential of PSSs. Therefore, in this paper, we make use of two best-in-class lean companies that are recognized for excellence in both product and service offerings in order to analyse PSS operations in light of lean thinking. As such, we adopt a multiple case study approach in order to propose a framework for lean product-oriented product–service systems.